AC-field Induced Gap Opening in the Vicinity of Extra Dirac Points in Band Structure of Graphene Superlattice - S.V. Kryuchkov; E.I. Kukhar' (Журнал нано- та електронної фізики)
Floquet spectrum of electrons in graphene superlattice subjected to the ac electric field was investigated. The ac-field vector was assumed to oscillate perpendicularly to the superlattice axis. In the vicinity of extra Dirac points of superlattice band structure the gap was shown to be dynamically induced by the ac-field. Such effects are due to the nonadditivity of the electron spectrum of graphene superlattice.